INTEGRASI METODE FUZZY ANALYTICAL HIERARCHY PROCESS (FAHP) DALAM PEMILIHAN KEBIJAKAN RISK BASED MAINTENANCE PADA MESIN DH2100 - Rahmad Wisnu Wardana; Bagus Mahendra Efendi; Ilyas Masudin (Jurnal Teknik Mesin dan Pembelajaran, 2023)
This study discusses the integration of Fuzzy Analytical Hierarchy Process (FAHP) method in the selection of Risk Based Maintenance (RBM) policy for DH2100 Machine at PT Fajar Putra Plasindo. The objective of this research is to enhance the effectiveness of maintenance strategies and optimize decision-making in RBM policy selection. The FAHP method is employed to address the uncertainties and complexities in maintenance decision-making. The results showed that a risk value of Rp. 83,365,100 was obtained or with a risk percentage of 0.1%. the percentage of the risk exceeds the established tolerance limit. So then the selection of maintenance actions is carried out using the FAHP, from the calculation results it is found that Condition Based Maintenance maintenance actions are the right maintenance actions for the DH2100 Machine.